Brain Injury and Mental Health Among the Victims of Intimate Partner Violence: A Case-Series Exploratory Study - Karakurt, Gunnur; Whiting, Kathleen; Jones, Stephen E.; Lowe, Mark J.; Rao, Stephen M. (Frontiers in Psychology, 2021)
Intimate partner violence (IPV) survivors frequently report face, head, and neck as their injury site. Many mild TBIs are undiagnosed or underreported among IPV survivors while these injuries may be linked to changes in brain function or pathology. Traumatic Brain Injury (TBI) sustained due to IPV often occurs over time and ranges in severity. The aim of this study was to explore risk factors, symptoms, and brain changes unique to survivors of intimate partner violence with suspicion of TBI. This exploratory serial case study examines the potential relationships among IPV, mental health issues, and TBI. Participants of this study included six women: 3 women with a history of IPV without any experience of concussive blunt force to the head, and 3 women with a history of IPV with concussive head trauma. Participants completed 7T magnetic resonance imaging (MRI) of the brain, self-report psychological questionnaires regarding their mental health, relationships, and IPV, and the Structured Clinical Interview. MRI scans were analyzed for cerebral hemorrhage, white matter disturbance, and cortical thinning. Results indicated significant differences in resting-state connectivity among survivors of partner violence as well as differences in relationship dynamics and mental health symptoms. White matter hyperintensities are also observed among the survivors. Developing guidelines and recommendations for TBI-risk screening, referrals, and appropriate service provision is crucial for the effective treatment of TBI-associated IPV. Early and accurate characterization of TBI in survivors of IPV may relieve certain neuropsychological consequences.